Physical Violence Against Age Children are Reviewed from The Age of Married Mother - Irawati, Irawati; Astuti, Henny Puji (Jurusan PGPAUD FIP UNNES, 2020)
This study aims to determine the differences in physical violence against children after an early age in terms of the age of the mother at marriage. The subjects of this study were children and mothers in the Jatirejo village, Gunungpati District, Semarang City. The number of samples in this study were 30 early childhood. Sampling in this study was using Purposive Sampling techniques. In this study, there was a formulation of the problem that there were differences in physical violence against early childhood in terms of the age of the mother, who married at the age according to the marriage law and married mothers not in accordance with the law marriage law. The data collection method used in this study is a quantitative method, the data in the form of scores are taken using a ratio scale that is the scale of physical violence against early childhood. The analysis technique used is parametric statistics with the help of statistics on the SPSS 20.0 for Windows program. The results of t-test results of the t value are 3.842 and the significance value is 0.001, tcount> t table (3.842> 1.701) and p value <0.05 which is (0.001 <0.05). This means that there are differences in the level of physical violence against early childhood in terms of the age of married mothers in respondents who marry not in accordance with the marriage law (young age) higher physical violence than physical violence against early childhood, in respondents married mothers at the age of law- marriage law (ideal age).